Imidacloprid affects rat liver mitochondrial bioenergetics by inhibiting FoF1-ATP synthase activity - Bizerra, Paulo F. V. [UNESP]; Guimarães, Anilda R. J. S. [UNESP]; Maioli, Marcos A. [UNESP]; Mingatto, Fábio E. [UNESP] (Taylor & Francis, 2018)
Imidacloprid (IMD) is a neonicotinoid insecticide widely used in crops, pets, and on farm animals for pest control. Several studies were conducted examining the adverse effects of IMD on animals often exhibiting hepatic damage. The aim of this study was to determine the effects of IMD on bioenergetics of mitochondria isolated from rat liver. Imidacloprid (50–200 µM) produced a concentration-dependent decrease in oxygen consumption and ATP production without markedly affecting mitochondrial membrane potential (MMP). Oxygen consumption experiments showed that IMD did not significantly affect the respiratory chain, and this was similar to findings with oligomycin and carboxyatractyloside, suggesting a direct action on FoF1-ATP synthase and/or the adenine nucleotide translocator (ANT). Imidacloprid inhibited FoF1-ATP synthase activity only in disrupted mitochondria and induced a partial inhibition of ADP-stimulated depolarization of the MMP. Our results indicate that IMD interacts specifically with FoF1-ATP synthase resulting in functional inhibition of the enzyme with consequent impairment of mitochondrial bioenergetics. These effects of IMD on mitochondrial bioenergetics may be related to adverse effects of this insecticide on the liver.